Our commitment to ethical principals - Moscoso, Manolete S. (2016)
We, who have the good fortune to be involved in the academic career and scientific work, clearly recognize that the dissemination of research data is the foundation for the advancement of science. This type of knowledge depends essentially on the behavior and integrity of researchers that regularly report their results and data, as well as the conduct and ethical accountability of the journal's editors, as well as the publishing organizations which participate, publish and directly support the reporting of empirical information to the community of scientists and professionals in the world. DOI: https://doi.org/10.24265/liberabit.2016.v22n2.01